2000
DOI: 10.1590/s0034-89102000000200008
|View full text |Cite
|
Sign up to set email alerts
|

Características das vítimas por acidentes de transporte terrestre em município da Região Sul do Brasil

Abstract: OBJETIVO: Avaliar a magnitude da morbimortalidade por acidentes de transporte terrestre e as características das vítimas. MÉTODOS: Foram estudadas 3.643 vítimas de acidentes de transporte terrestre ocorridos em Londrina, Paraná, no primeiro semestre de 1996, abrangendo as registradas pela Polícia Militar, as que morreram no local do evento ou no trajeto para o hospital, além das atendidas em serviços de pronto-socorro ou internadas pelo Sistema Único de Saúde. Foi observado um prazo de 180 dias para verificar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
69

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 8 publications
4
27
0
69
Order By: Relevance
“…This is aggravated by the fact that young people generally consume more alcohol and drugs than adults of more advanced age, and tend to exceed speed limits and ignore other traffic safety standards more, which increases the chances of accidents (8)(9) . In a study carried out in Londrina in the year 2000, it was verified that 65.6% of male young people had already been involved in traffic accidents, 15.6% had already participated in street races and 44.6% had consumed alcoholic beverages and driven a vehicle afterwards in the last 30 days (10) . Another study in the South of Brazil, carried out between 1997 and 2000, indicated that the predominant age range in traffic accidents, with more than 70.0%, was between 10 and 39 years (11) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is aggravated by the fact that young people generally consume more alcohol and drugs than adults of more advanced age, and tend to exceed speed limits and ignore other traffic safety standards more, which increases the chances of accidents (8)(9) . In a study carried out in Londrina in the year 2000, it was verified that 65.6% of male young people had already been involved in traffic accidents, 15.6% had already participated in street races and 44.6% had consumed alcoholic beverages and driven a vehicle afterwards in the last 30 days (10) . Another study in the South of Brazil, carried out between 1997 and 2000, indicated that the predominant age range in traffic accidents, with more than 70.0%, was between 10 and 39 years (11) .…”
Section: Resultsmentioning
confidence: 99%
“…This high danger level, however, is unparalleled in international literature, which mentions three to four times more accidents involving cars than motorcycles (14) . Studies in Londrina also appoint motorcyclists as the main traffic accident victims, with more than 40.0%, including survivors and lethal victims (10) .…”
Section: Resultsmentioning
confidence: 99%
“…Existem doenças em que apenas os casos mais graves e/ou associados com outras morbidades são hospitalizados como distúrbios psiquiátricos 30,66 , diarréias 61 , doença de Chagas 37 , dengue 34,43 , hanseníase, tuberculose, coqueluche, sarampo e hepatite 45 . Para as doenças coronarianas 22,31,60 , traumas, lesões e envenenamentos 27,32,33,38 , a principal limitação reside no fato de que são freqüente-mente atendidos em emergências, não sendo, portanto, incluídos na AIH. Em situação oposta encontram-se as patologias que necessariamente requerem internação como as meningites, raiva humana, tétano, sífilis congênita, difteria, febre tifóide, leptospirose, AIDS, leishmaniose visceral, cólera e fratura de colo de fêmur.…”
Section: Resultsunclassified
“…Em Londrina, em 1996, os motociclistas corresponderam a 44,4% das 3.643 vítimas 6 . Outra investigação, no mesmo município, analisando o período compreendido entre 1997 e 2000, traz os motociclistas como as principais vítimas do trânsito atendidas por serviço de atenção pré-hospitalar em todos os anos, com valores sempre superiores a 40% 7 .…”
Section: Introductionunclassified
“…A utilização da motocicleta no mercado formal ou informal de trabalho, especialmente em serviços de tele-entrega de mercadorias e documentos (motoboys) ou transporte de passageiros (mototáxis), é referida por diversos autores como possível causa para o aumento do número de ví-timas motociclistas 1,6,9,10 .…”
Section: Introductionunclassified